Artificial Intelligent Architecture Analysis in Life Insurance Company - Boy Bismar; Heru Purnomo Ipung; Eka Budiarto (Sahabat Publikasi, 2026)
The life insurance industry faces increasing challenges due to complex processes, growing customer expectations, and competitive pressures. This research explores the transformative potential of Artificial Intelligence (AI) in revolutionizing end-to-end processes within the life insurance sector. By leveraging AI technologies such as machine learning, predictive analytics, and natural language processing, insurers can address inefficiencies in underwriting, claims processing, policy changes, and renewals—improving both speed and accuracy while ensuring regulatory compliance. The study adopts a comprehensive research methodology using TOGAF, beginning with a literature review and user interviews to identify existing challenges and inefficiencies in life insurance processes. A detailed architecture vision was developed using fishbone analysis and solution concept diagrams. Business and technology architectures were designed to address gaps, leveraging AI-driven tools to enhance risk assessment, fraud detection, and customer engagement. Expert validation was incorporated to ensure the practical applicability of the proposed solutions. The research presents an AI architecture tailored to various life insurance processes, including proposal creation, new business/underwriting, renewal, policy changes, claims management, agent commission, financial report, premium reserve, and reinsurance. Key innovations include predictive models for risk scoring, fraud detection algorithms, and churn prediction models to enhance customer retention. The study highlights the significance of AI-driven personalization, operational efficiency, and decision-making in optimizing these processes. The findings emphasize the importance of aligning AI integration with organizational goals and compliance standards. AI not only expedites processing but also enhances customer satisfaction and competitiveness in a rapidly evolving market.